A framework for quantifying the extent of impact to plants from linear construction - Jun Xiao (Nature Portfolio, 2017)
Abstract We present a novel framework that accurately evaluates the extent of a linear project’s effect from the variability of the structure of the plant community while avoiding interference caused by pioneer species and invasive species. This framework was based on the change of dominant species in the plant community affected by construction. TWINSPAN classification and variation of the integrated importance value (IIV) of each plant species group were used to characterize the process of change in the structure of the plant community. Indicator species group and its inflection point were defined and used to judge the extent of the effects of pipelines. Our findings revealed that dominant species in the working area of the pipeline construction were different from the original plant communities. With the disturbance decreased, the composition and structure of the plant communities gradually changed. We considered the outer limit of the area affected by the construction to be the first area in which the plant community reached a steady state and was similar to the original community. The framework could be used in the post eco-environment impact assessment of linear construction to estimate the intensity of disturbance and recovery condition.